في مدينة البصرة , جنوب العراق(Co)تمثيل كارتوغرافي لمستويات وتأثيرات التلوث بغاز أحادي أوكسيد الكربون - Karmalla, Hassen A. (University of Thi-Qar Journal of Science, 2013)
This study aims at the cartographic representation for the concentrations of carbon monoxide (CO)measured in ambient air of Basra City, by using a calibrated portable QREA II gas monitor. Measurementshave been carried out for three days during Mar/2012, in 34 sampling stations which have been selected onan equal-distance grid of the study area map. A cartographic representation of the recorded values for thispollutant has been applied, in the way of isoclines, and an accurate identification could been obtained forspatial variability of the levels and impacts of carbon monoxide pollutant, and the affected areas have beenexactly calculated, as well as actual number of affected population has been estimated. The present studyconcluded that about three quarter of the surveyed areas and habitants may be suffered from the studiedpollutant, and that this problem perhaps worsens in accompanying with the anticipated rise in gaseousemissions released into the urban environment of the study area.